2004
DOI: 10.1002/hipo.20022
|View full text |Cite
|
Sign up to set email alerts
|

Two reentrant pathways in the hippocampal‐entorhinal system

Abstract: The entorhinal cortex has long been recognized as an important interface between the hippocampal formation and the neocortex. The notion of bidirectional connections between the entorhinal cortex and the hippocampal formation have led to the suggestion that hippocampal output originating in CA1 and subiculum may reenter hippocampal subfields via the entorhinal cortex. To investigate this, we used simultaneous multi-site field potential recordings and current source density analysis in the entorhinal cortex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 47 publications
7
63
2
Order By: Relevance
“…Our study confirmed previous anatomical (HjorthSimonsen, 1971;Swanson and Cowan, 1977;Sorensen and Shipley, 1979;Tamamaki and Nojyo, 1995;Ino et al, 2001) and physiological findings (Kohler, 1985;Finch et al, 1986;Van Groen and Lopes da Silva, 1986;Jones, 1987;Bartesaghi et al, 1989;Kloosterman et al, 2003bKloosterman et al, , 2004, and demonstrates that the hippocampal input into the m-EC excite neurons in the deep layers V and VI. The deep neuron EPSP/spike correlated with a current sink at 800 -1000 m depth (layers V-VI), which represents the first population event generated in the m-EC after the hippocampal response (Bartesaghi et al, 1989;Kloosterman et al, 2003b).…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirmed previous anatomical (HjorthSimonsen, 1971;Swanson and Cowan, 1977;Sorensen and Shipley, 1979;Tamamaki and Nojyo, 1995;Ino et al, 2001) and physiological findings (Kohler, 1985;Finch et al, 1986;Van Groen and Lopes da Silva, 1986;Jones, 1987;Bartesaghi et al, 1989;Kloosterman et al, 2003bKloosterman et al, , 2004, and demonstrates that the hippocampal input into the m-EC excite neurons in the deep layers V and VI. The deep neuron EPSP/spike correlated with a current sink at 800 -1000 m depth (layers V-VI), which represents the first population event generated in the m-EC after the hippocampal response (Bartesaghi et al, 1989;Kloosterman et al, 2003b).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the projection from the entorhinal cortex to area CA1 can sustain NMDA receptor-dependent LTP following 100 Hz HFS (Remondes and Schuman, 2003). Additionally, the return projection from the hippocampus to the entorhinal cortex can also carry electrophysiological information (Ivanco and Racine, 2000;Kloosterman et al, 2003aKloosterman et al, , 2004. Moreover, the CA1 to entorhinal and subiculum to entorhinal projections (Craig and Commins, 2006) are both capable of sustaining short-and long-term changes in synaptic plasticity.…”
Section: Hippocampal and Parahippocampal Projectionsmentioning
confidence: 99%
“…Based on anatomy (Swanson and Cowan, 1977;Wyss, 1981;Kosel et al, 1982Kosel et al, , 1983Deacon et al, 1983;McIntyre et al, 1996;Naber et al, 1997Naber et al, , 1999Naber et al, , 2000Naber et al, , 2001aBurwell and Amaral, 1998a;Kloosterman et al, 2003b) and physiology (Canning et al, 2000;Ivanco and Racine, 2000;de Curtis and Biella, 2002;Garden et al, 2002;Kloosterman et al, 2003aKloosterman et al, , 2004, 2006, 2007Commins, 2009, 2010), the hippocampal-parahippocampal network has been proposed as a relay of parallel pathways between the hippocampus and the constituents of the parahippocampal region that may play a role in learning and memory (Witter et al, 2000a,b;Witter, 2002). Our lab has shown previously that the projections originating in the distal CA1 and proximal subiculum which terminating in the lateral entorhinal cortex show a greater tendency to sustain 'electrophysiologically excitatory' synaptic plasticity (demonstrating a greater tendency to show potentiation, even at low frequency stimulation levels) whereas those originating in the proximal CA1 and terminating in the medial entorhinal cortex show a greater tendency to sustain 'electrophysiologically inhibitory' synaptic plasticity (readily demonstrating LTD, see Craig and Commins, 2007).…”
Section: Anatomical and Electrophysiological Evidence For Segregationmentioning
confidence: 99%
“…The multimodal sensory information received by the EC is processed and via output neurons in the superficial layers projected to the hippocampus (Steward and Scoville 1976;Gloveli et al 1997). Hippocampal projections to the deep layers of EC contribute return connectivity (Kloosterman et al 2004). The entorhino-hippocampal circuitry is completed by intrinsic neurons connecting deep to superficial layers of EC (Gloveli et al 2001;van Haeften et al 2003).…”
Section: Introductionmentioning
confidence: 99%